Global regulatory issues for the cosmetics industry. - Betton, C. I.; Lintner, Karl.; ScienceDirect eBooks (Norwich, N.Y. : William Andrew ; Oxford : Elsevier Science [distributor], 2007)
This second volume examines regulatory issues of ingredients, manufacturing, and finished products, as well as claim substantiation, packaging, and advertising. A chapter on Chinese regulations will be one of the first about this country to be published in book form. . Includes a regulatory map of India and China . Global IP protection strategies . REACH and European Regulatory standards . "Green chemistry" in relation to cosmetics and regulation * Simplifies global regulations for anyone exporting cosmetics. * Excellent reference not only for manufacturing and marketing, but for legal departments and packaging as well. * Describes how to develop a global regulatory strategy.
Volume 1. Cosmetic risk assessment / C.I. Betton ; Regulatory developments in Canada, Japan, China, and Australia / Janet Winter Blaschke ; Registration, evaluation, authorization, and restriction of chemicals : the new EU regulation / C.I. Betton ; Emerging global regulatory trends impacting the health and beauty industry / Ken Rivlin, Jochem Spaans, and Felise Cooper ; Developing a global regulatory strategy : leveraging local knowledge to drive rapid market entry / Neil Wilcox ; Toxicity of cosmetics : regulatory requirements / Harold I. Zeliger ; Restricted substances in consumer goods / Ruud Overbeek ; Non-animal testing methodology / Ray Boughton ; Nanomaterials in personal care products and FDA regulation / George A. Kimbrell -- Volume 2. Green chemistry : foundations in cosmetic sciences / Amy S. Cannon and John C. Warner ; REACH--life in and outside the EU : how REACH will affect the supply chain / Ruud A. Overbeek, Bruce Calder, Michael Fry, and Roman Humeniuk ; Cosmetic ingredients : definitions, legal requirements, and an attempt to harmonize (global?) characterization / Karl Lintner ; "26 allergens" in cosmetics : a challenge for all stakeholders / Christine Bertram ; Manufacturing cosmetic ingredients according to good manufacturing practice principles / Iain Moore ; Safe cosmetics and regulatory compliance : from burden to opportunity (cosmetics as vectors for bioterrorists?) / Preston W. Blevins ; Cosmeceutical (antiaging) products : advertising rules and claims substantiation / Wen Schroeder ; Cosmetic claim substantiation : methods and legal framework / Philippe Masson, Philippe Mondon, and Karl Lintner ; The impact of global regulations on packaging / Holly C. Young and Marcus Tirado ; Global cosmetic regualtions? a long way to go ... / Sandra B. Schneider ; Global patent and trade mark strategies : a must for everybody? / Estelle Haeffner, Virginie Gliubislavich, and Karl Lintner.
Volume 1 editor: C.I. Betton; volume 2 editor: Karl Lintner.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Cosmetics -- Law and legislation; Cosmetics industry -- Law and legislation; Cosmetics industry -- Law and legislation; Cosmetics -- Law and legislation; Electronic books